2019
DOI: 10.3390/nu12010099
|View full text |Cite
|
Sign up to set email alerts
|

Potential Beneficial Effects of Vitamin D in Coronary Artery Disease

Abstract: Vitamin D plays a pivotal role in bone homeostasis and calcium metabolism. However, recent research has indicated additional beneficial effects of vitamin D on the cardiovascular system. This review aims to elucidate if vitamin D can be used as an add-on treatment in coronary artery disease (CAD). Large-scale epidemiological studies have found a significant inverse association between serum 25(OH)-vitamin D levels and the prevalence of essential hypertension. Likewise, epidemiological data have suggested plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 95 publications
(102 reference statements)
1
29
1
4
Order By: Relevance
“…The authors concluded that it was not clear if vitamin D supplementation has any benefits on the objectives analyzed and that data from observational studies should not be used to support the use of the vitamin to prevent disease in healthy persons [ 142 ]. Neither have CV improvements emerged following supplementation with cholecalciferol in the results of a recent review [ 143 ] and meta-analysis including more than 83,000 individuals, in which no benefits of vitamin D were observed in terms of protection against CVD events [ 144 ].…”
Section: Vitamin D Improves Cv Healthmentioning
confidence: 99%
“…The authors concluded that it was not clear if vitamin D supplementation has any benefits on the objectives analyzed and that data from observational studies should not be used to support the use of the vitamin to prevent disease in healthy persons [ 142 ]. Neither have CV improvements emerged following supplementation with cholecalciferol in the results of a recent review [ 143 ] and meta-analysis including more than 83,000 individuals, in which no benefits of vitamin D were observed in terms of protection against CVD events [ 144 ].…”
Section: Vitamin D Improves Cv Healthmentioning
confidence: 99%
“…In the context of these findings, there is a need for randomized controlled trials documenting this process in the general population. Despite this early data, vascular inflammation has not yet been decisively associated with vitamin D deficiency or vitamin D supplementation [ 74 , 75 ].…”
Section: Vitamin D’s Action On Atherosclerosismentioning
confidence: 99%
“…The beneficial role of its supplementation after myocardial infarction has been showed in vitro studies [66][67][68]. However, most randomized controlled trials (RCTs) conducted in the adult population have shown no beneficial effects of vitamin D supplementation in preventing cardiovascular diseases or reducing cardiovascular risk [21,[69][70][71][72][73]. It is still not clear whether calcitriol or other potent vitamin D analogues might have major effects and whether specific subgroups of patients, such as type 2 diabetic subjects with CAD, might benefit most from vitamin D supplementation [69][70][71][72][73].…”
Section: The Impact Of Vitamin D Supplementationmentioning
confidence: 99%